Poly amino acid thermosensitive hydrogel loaded with ICG-001 for inhibiting keloid by down-regulating the Wnt/β-Catenin pathway. (October 2022) - Sheng, Fan; Luo, Yinli; Wu, Di; Yuan, Jiachen; Zheng, Ge; Zheng, Yuhao; Jin, Zhehu
Graphical abstract: Highlights: For the first time, the inhibitory effect of ICG-001 on keloids was evaluated by in vitro and in vivo experiments. The new gel can reduce side effects while maintaining the local drug concentration and improve the tumor inhibition effect. The mechanism of ICG-001 on proliferation, invasion and excessive collagen deposition of human keloid cells was analyzed. Abstract: Keloids are benign tumors that appear as abnormal fibrous proliferations on the surface of the skin. A full understanding of the causation between key cells and molecules in the pathogenesis of scarring is required. This research aims to adopt the influence of the small molecule inhibitor ICG-001 of Wnt/β-catenin signaling pathway on the proliferation, invasion, and apoptosis of human keloid fibroblasts, and on the excessive deposition of collagen in human keloid fibroblasts, and the effect of on excessive collagen deposition and fibrosis in human keloid fibroblasts. It also aims to inject the polyamino acid thermosensitive hydrogel with contains ICG-001 drug around Keloid model in nude mice, exploring its inhibitory effect on tumor growth. The ICG-001 polyamino acid thermosensitive hydrogel material synthesized in this experiment can be injected into the vicinity of keloid and maintain the local drug concentration for a long time. As an inhibitor of Wnt/β-catenin signaling pathway, ICG-001 showed good effects of inhibiting the proliferation and promoting apoptosis of human keloid fibroblasts. The temperature-sensitive gel can be used to release the drug slowly, reducing the toxic and side effects of the drug. At the same time, because the material itself is non-toxic, this drug loaded gel has good therapeutic effect on keloids.